Pengaruh Kekhawatiran Privasi dan Kecemasan Teknologi terhadap Niat Beli Melalui Kepercayaan di Kalangan Pengguna Shopee di Kota Malang - Aditya Putra Wardanu; Sudarmiatin; Titis Shinta Dhewi (Universitas Muhammadiyah Pontianak, 2026)
The rapid growth of e-commerce raises concerns regarding personal data control and technological anxiety, potentially affecting trust and purchase intention among Shopee users. This study aims to analyze the effects of perceived control and technological anxiety on purchase intention, with trust as a mediating variable. Using a quantitative approach and PLS-SEM, data were collected from 386 Shopee users. The results indicate that perceived control positively affects trust and purchase intention, while technological anxiety has negative effects. Trust also significantly mediates relationships. These findings emphasize the importance of secure systems and transparent privacy policies to enhance consumer trust. Keywords: Privacy Concerns; Technological Anxiety; Trust; Puchase Intention; Shopee